Analysis of The Quality of Essay Problems in Class IX in The History of Islamic Culture - Al Zahra, Ashma Tazkiya (Jurnal Keprofesian Guru Keagamaan, 2023)
This study aims to analyze essay questions in Islamic Cultural History textbooks for Class IX MTs published by the Directorate of KSKK Madrasah, Directorate General of Islamic Education, Ministry of Religion of the Republic of Indonesia, whether the items fall under the HOTS or LOTS criteria and whether this book is suitable for use by students or not. The method used is a qualitative method using a descriptive approach. Based on the results of the research conducted, it was stated that the number of questions studied was 35 essay questions in 7 chapters. There are 9 questions included in the Higher Order Thinking Skill category, 7 questions in the MOTS category and 19 questions in the LOTS category. The conclusions that can be drawn are that the questions are categorized in LOTS questions, namely 54.3%, the criteria for HOTS questions are 25.7% and those that are categorized as MOTS questions are 20%. The implication is that the Islamic Cultural History book that is analyzed can be used in training for the preparation of HOTS research questions and is suitable for use.